TRANSLATING SCIENCE FICTION AND FANTASY: CHALLENGES AND PECULIARITIES - Tereshchenko, Liliia (Collection of scientific papers «ΛΌГOΣ», 2025)
The article describes the main challenges faced by translators when working with texts belonging to the fantasy and science fiction genres. The genre-specific nature of texts significantly affects their stylistic and lexical-semantic characteristics, which requires special attention and the search for the best strategies on the part of the translator.